Analysis of Sustainability Reporting as the Implementation of Sustainability Accounting at PT Unilever Indonesia TBK in 2024 - Sheila Fatimah Majid; Fetty Kurnia Dewi; Wulan Budi Astuti (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This academic study examines the implementation of sustainability accounting through the comprehensive evaluation of the sustainability report published by PT Unilever Indonesia Tbk in the fiscal year of 2024. Employing a qualitative descriptive approach with systematic document analysis, the research evaluates the corporate report against the Global Reporting Initiative Standards and Indonesian regulatory frameworks. The empirical analysis reveals that the company successfully integrates its core corporate business strategy into the newly established Growth Action Plan framework, driving substantial and highly measurable progress across critical environmental and social action areas. Specifically, the company achieved a ninety two percent reduction in greenhouse gas emissions relative to its baseline and successfully collected over ninety thousand tons of postconsumer plastic waste. While these environmental disclosures reinforce social legitimacy and demonstrate strong stakeholder accountability, the reporting still demonstrates an unbalanced emphasis on positive milestones over negative operational impacts. Ultimately, this academic research provides valuable insights into corporate accounting practices by thoroughly evaluating material topic identification, independent external assurance verification, and domestic regulatory multiframework integration processes.